Social deprivation and prognosis in Scottish patients with pulmonary arterial hypertension. Issue 2 (1st February 2018) - Pellino, Katherine; Kerridge, Simon; Church, Colin; Peacock, Andrew J.; Crowe, Timothy; Jayasekera, Geeshath; Johnson, Martin K.; MacKenzie, Alison M.
Several demographic and clinical factors have prognostic significance in idiopathic pulmonary arterial hypertension (IPAH). Studies in China and the USA have suggested an association between low socioeconomic status and reduced survival. The impact of social deprivation on IPAH survival in the UK is not known. 280 patients with IPAH and hereditary PAH (HPAH) attending the Scottish Pulmonary Vascular Unit (Glasgow, UK) were assigned to social deprivation quintiles using the Scottish Index of Multiple Deprivation database. The association between survival and social deprivation quintile was assessed using Cox proportional hazards regression analysis. The distribution of IPAH/HPAH patients was more socially deprived than would be expected based on Scottish citizenry as a whole (Chi-squared 16.16, p=0.003), suggesting referral and access to care is not impeded by socioeconomic status. Univariate analysis demonstrated no significant association between social deprivation and survival (p=0.81), and this association failed to reach significance with inclusion of time, sex and age as covariates in the model (p=0.23). There were no statistically significant correlations between social deprivation and baseline clinical variables of prognostic importance except for age, sex and quality of life. Social deprivation is not a significant referral barrier or prognostic factor for IPAH and HPAH in Scotland. Social deprivation is not a significant referral barrier or prognostic factor for IPAH and HPAH in Scotland http://ow.ly/N7aL30gE4ui